Time and Cost Performance in Construction Projects in Southern and Central Regions of Peninsular Malaysia - Aftab Hameed Memon; Ismail Abdul Rahman; Ade Asmi Abdul Azis (International Journal of Advances in Applied Sciences, 2012)
Time and cost performance is the fundamental criteria for success of any project. Unfortunately construction industry in Malaysia has been regarded as industry facing poor performance leading to failure in achieving effective time and cost performance. As a consequence most of the project face huge amount of time and cost overrun. This study assessed the time and cost performance of construction projects in Malaysia using structured questionnaire survey. The findings of study revealed that 92% of construction projects were overrun and only 8% of project could achieve completion within contract duration. The amount of time overrun was in between 5-10% as agreed by respondents. In terms of cost performance only 11% of respondents mentioned that normally their projects are finished within the budgeted cost while 89% of respondents agreed that their projects were facing the problem of cost overrun with average overrun at 5-10% of contract price.  The major contributors of this poor performance include design and documentation issues, financial resource management and project management and contract administration issues. Further, qualitative study was carried out using semi-structured interviews with the experience personnel involving in managing construction project which resulted in developing 13 mitigation measure to improve time performance and 15 mitigation measure to improve cost performance in construction project. This study will help the practitioners to implement the mitigation measure at planning stage in order to achieve successful construction projects.